Recent molecular techniques to strengthen ecological studies in echinoderms - Rodríguez-Barreras, Ruber (Revista de Biología Tropical, 2024)
Introduction: Echinoderms, an integral component of marine ecosystems worldwide, have captivated scientific interest for centuries. Despite this longstanding attention, comprehending key facets such as trophic relationships, diet composition, and host-microbiota relationships still represents a challenge using traditional techniques. Recent years, however, have witnessed a transformative shift, thanks to the emergence of advanced molecular techniques, offering new approaches to strengthen ecological studies in echinoderms. Objective: Explore how recent advancements in molecular tools have impacted ecological research on echinoderms. Specifically, we aim to investigate the potential of these tools to shed light on trophic interactions, diet composition, and the characterization of gut microbial communities in these organisms. Methods: Available literature was used to clarify how novel molecular techniques can improve ecological studies. The focus is diet, trophic relationships, and gut microbiota. Results: Traditionally, studies of stomach contents using compound microscopy have provided an idea of ingested material; nevertheless, sometimes a simple magnified visualization of dietary content does not allow exhaustive identification of the entire food spectrum, as it is limited due to the rapid digestion and maceration of food items within the echinoderm’s digestive tract. The use of DNA-metabarcoding, targeting specific DNA regions, such as the mitochondrial COI gene, has allowed us to enhance the accuracy and precision of diet characterization by enabling the identification of prey items down to the species or even genetic variant level, providing valuable insights into specific dietary preferences. Another approach is the use of stable isotopes, particularly carbon and nitrogen, which provide a powerful tool to trace the origin and flow of nutrients through food webs. By analyzing the isotopic signatures in muscular tissues and food items, we can discern the sources of their primary food items and gain insights into their trophic position within the ecosystem. Lastly, a third new technique used to elucidate the characterization of the prokaryotic community is 16S rRNA sequencing. This method allows us to explore the composition and dynamics of the digestive tract microbial communities. Conclusions: This is a promising era for ecological research on echinoderms, where advances of molecular tools have enabled an unprecedented level of detail, resolving longstanding challenges in comprehending their trophic interactions, diet composition, and host-microbiota relationships, and opening new avenues of investigation in ecological studies.